Knowledge and Practices of General Public in Context to Canine Rabies - Irum, Shazia; Qayyum, Aamir; Javed, Maryam; Abdullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To estimate knowledge and practices of general public in context to canine rabies. Study Design: Retrospective study. Place and Duration of Study: Department of Nephrology, Mayo Hospital, Lahore 1st January 2020 to 30th June 2020. Methodology: Based on variance in topography and high animal acquaintance, the area was divided into four cardinal points and 50 respondents were taken from each area. A well-structured questionnaire was designed for entering the required information in form of open ended questions regarding their knowledge and general practices. All the responses were categorized and further decoded for extracting related information. Results: There were 127 male and 73 female respondents. The mean age was 29.3±3.5 years with 52% within the age group of 26-35 years. Only 44% respondents were known about clinical symptoms of rabies. Almost half of the respondents had their pets vaccinated while other half did not vaccinate their pet/pets against rabies. Conclusion: More awareness program should be conducted for increasing knowledge of general public against rabies disease.